L2 Writing Strategies Used by EFL Graduate Students - Arifin, Syaadiah (Journal of ELT Research, 2017)
This study investigates the writing strategies and the predominantly strategies used by four Indonesian graduate students when writing in L2 (English). They were divided into 2 groups, skilled and less skilled writers, to examine what strategies they applied when writing. The main instrument of this study is Think Aloud Protocols (TAPs). The analysis of data collected discovered some findings: (1) both skilled and less skilled writers used varied strategies. However, the frequency of using each strategy was different. Skilled writers used each strategy in high frequency. On the other hand, less skilled writers only used each strategy in low frequency, while skilled writers understand the recursive nature of writing. (2) Skilled writers used reading and rereading strategies in high frequency for several purposes: revising and editing the text, developing ideas, and getting new ideas, while less skilled writers rarely used those strategies. They wrote whatever ideas came into their mind, and reread the text once in a while. These findings suggest that effective writing strategies should be introduced explicitly when student writers have already mastered the foundation of writing. Unfortunately, they are seldom guided on the use of writing strategies in the process of their writing. In fact, effective writing strategies and the frequency of using each strategy could help them become good writers and influence the quality of their writing. Based on these findings some suggestions are discussed.